2011
DOI: 10.5146/tjpath.2010.01043
|View full text |Cite
|
Sign up to set email alerts
|

Profile of gallbladder diseases diagnosed at afyon kocatepe university: a retrospective study

Abstract: Objective: Superficial tumors including Ta, Tis, and T1 make up 75% of urothelial carcinomas of the bladder. While the behavior of these superficial urothelial cancers is relatively benign, invasive tumors have a significant mortality rate. However, Ta and T1 tumors might display different biological behavior. There is therefore a great need for biomarkers that can accurately distinguish the behavior of urothelial carcinomas in addition to tumor grade and stage. our aim was to determine the immunohistochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 36 publications
(30 reference statements)
4
7
0
3
Order By: Relevance
“…These ratios were higher when compared to the Mazlum et al . study, which reported 13.3% of cholesterolosis cases from the Western part of Turkey [10]. Parallel to our study, Bolat et al .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These ratios were higher when compared to the Mazlum et al . study, which reported 13.3% of cholesterolosis cases from the Western part of Turkey [10]. Parallel to our study, Bolat et al .…”
Section: Discussionsupporting
confidence: 90%
“…Cholesterol polyps are one of the most frequent types stated in various studies [10,12,13]. Similar to the literature, we detected 16 (3.2%) polyps in Group 2 with the increased sample size, and 11 (2.5%) of those were cholesterol polyps.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…One sample was used for the rapid urease test (Pronto Dry), the second for aerobic and anaerobic culture, and the third for histopathologic evaluation. Gallstones were classified as cholesterol, pigment, and mixed stones based on their color and consistency [14, 15]. …”
Section: Methodsmentioning
confidence: 99%
“…of age.Mohan et al [11] found that the age of the patients varied from 10 to 90years with maximum number of cases between 31 and 40 years of age. Mazlum M et al [12] also noted male to female ratio being 1:2.33. Singh A 13], Raza [14] and Udwadia [15] found the maximum incidence in the age group between 3 rd to 5 th decades.…”
Section: Discussionmentioning
confidence: 91%